Non-equilibrium electrokinetic micromixer with 3D nanochannel networks1. Issue 8 (21st April 2015) - Choi, Eunpyo; Kwon, Kilsung; Lee, Seung Jun; Kim, Daejoong; Park, Jungyul
<x xml:space="preserve">Abstract</x> An active micromixer having 3D nanochannel networks constructed from a spatially controlled nanoparticle assembly is proposed. It induces vortex generation due to non-equilibrium electrokinetics near the NCNM that allow a large effective interfacing area.